TREATMENT FOR GASTROESOPHAGEAL REFLUX DISEASE AMONG CHILDREN, SUFFERING FROM JUVENILE ARTHRITIS - T.M. Bzarova; P.L. Shcherbakov; E.I. Alexeeva; E.G. Chistyakova; S.I. Valieva ("Paediatrician" Publishers LLC, 2007)
The article presents the evaluation results of esomeprazol efficacy in the complex therapy for gastroesophageal reflux disease among 152 children aged between 3 and 18, suffering from juvenile arthritis. The treatment scheme used in treatment induced the remission of gastro esophageal reflux disease among 45% of patients, conduced to considerable decrease of the esophagus affect intensity among 53% of patients, epithelized erosions of the mucous coat of esophagus among 30 of 32 children. The medication did not cause any clinically significant side responses among the cured children (even younger ones) and may be applied to treat gastro esophageal reflux disease among the patients, suffering from juvenile arthritis.Key words: gastroesophageal reflux disease, children, treatment, reflux, esomeprazol, esophagitis, juvenile rheumatoid arthritis.